KEBERLAKUAN KONSEP "SCANDALIZING THE COURT" DALAM HUKUM POSITIF - Kholilur Rahman; Risang Aji Baskoro Putro (Realism: Law Review, 2023)
Insulting judges and courts not only occurs during court proceedings, but can also be done outside the courtroom through media or publications. The term Scandalizing the Court is actually part of contempt out of court, but is specifically aimed at undermining the authority of judges or courts. This article will discuss an overview of the concept of Scandalizing the Court, followed by a discussion of efforts to regulate violations of Scandalizing the Court after the enactment of the National Criminal Code. The research method used is normative, using a statutory approach, conceptual approach, and comparative approach. The results of the study conclude, firstly, that the philosophical principles or foundations regarding the issue of defamation, especially the concept of Scandalizing the Court, are to maintain the atmosphere of honor in the courts and to protect society from attempts to make the courts appear shameful in the eyes of the public. Secondly, various efforts to regulate violations of Scandalizing the Court in Indonesia have been carried out by the legislature, as the Criminal Code (WvS NI) is not sufficient to accommodate violations that attack the integrity and impartiality of the courts (Scandalizing the Court).